Emergence of varicella-zoster virus resistance to acyclovir: epidemiology, prevention, and treatment. Issue 11 (2nd November 2021) - Shiraki, Kimiyasu; Takemoto, Masaya; Daikoku, Tohru
ABSTRACT: Introduction : Acyclovir has led to the development of successful systemic therapy for herpes simplex virus and varicella-zoster virus (VZV) infection, and the use of valacyclovir and famciclovir has improved treatment. Additionally, the use of a helicase-primase (HP) inhibitor (HPI), amenamevir, is changing the treatment of herpes zoster (HZ). Area covered : VZV infection is prevented by vaccines and is treated with antiviral agents. Acyclovir and penciclovir are phosphorylated by viral thymidine kinase and work as chain terminators. Improvements in the management of immunocompromised patients have reduced severe and prolonged immunosuppression and chronic VZV infection with acyclovir-resistant mutants has become rarer. The HP is involved in the initial step of DNA synthesis and amenamevir has novel mechanisms of action, efficacy to acyclovir-resistant mutants, and pharmacokinetic characteristics. The literature search for PUBMED was conducted on 10 April 2020 and updated on 4 November 2020. Expert opinion : Amenamevir has been used to treat HZ in Japan. Although the number of patients with VZV infection will decrease owing to the use of vaccines, the addition of HPI will improve treatment and treatment options for resistant viruses. The clinical use of HPIs in addition to current nucleoside analogs opens a new era of antiherpes therapy.